LABOR AND EMPLOYMENT OF YOUTH IN THE ARCTIC ZONE OF RUSSIA: SOCIO-CULTURAL AND ECONOMIC ASPECTS (CASE OF ARKHANGELSK AGGLOMERATION) - Lyudmila A. Chizhova; Olga V. Lets; Andrey O. Podoplekin (Russian Studies in Law and Politics)
Background. The article is describes the problems and peculiarities of labor and employment of the younger generation in the Arctic regions of Russia in the context of modern political, economic and socio-cultural reality. Special attention is paid to the results of a sociological study of the youth of the Arkhangelsk agglomeration, where the risks of job instability are quite acute, which in turn leads to high rates of migration attitudes.